CIRI FONOLOGI BAHASA ANAK TUNAGRAHITA (STUDI KASUS DUA SISWA SMP YIMA ISLAMIC SCHOOL BONDOWOSO) - Sabdaniyah, Ufinatus; Wibisono, Bambang; Asrumi, Asrumi (Pusat Pengembangan Bahasa IAIN Tulungagung, 2020)
This research examines the phonological characteristics of mild mental retardation children from a psycho-language perspective. The approach used in this study is a qualitative approach, because the object under study is a phenomenon of human language and the data used are descriptive data. This research was conducted at Yima Islamic Middle School, located in Bondowoso Regency, East Java. This study involved two students who were mentally retarded at the school. Data collection was carried out by listening methods, interview techniques, and field techniques. Data analysis is performed through categorization, data presentation, data description, and interpretation. From the results of the study, it was found that there were some sounds that could not be pronounced perfectly by the research object, and the object of the study had an error in articulating the sounds of the vocal and consonant sound groups. The conclusion of this study is that errors in the language phonological articulation of mentally retarded children are caused by several factors, namely genetic factors, physical symptoms when infants and toddlers, mistakes in assuming food intake by the mother, and lack of stimulus from parents in stimulating the communicative side of children.